The effects of chronic mitragynine (Kratom) exposure on the EEG in rats - Suhaimi, Farah Wahida; Hassan, Zurina; Mansor, Sharif Mahsufi; Müller, Christian P. (Neuroscience Letters, 2021)
Mitragynine is the main alkaloid isolated from the leaves of Mitragyna speciosa Korth (Kratom). Kratom has been widely used to relieve pain and opioid withdrawal symptoms in humans but may also cause memory deficits. Here we investigated the changes in brain electroencephalogram (EEG) activity after acute and chronic exposure to mitragynine in freely moving rats. Vehicle, morphine (5 mg/kg) or mitragynine (1, 5 and 10 mg/kg) were administered for 28 days, and EEG activity was repeatedly recorded from the frontal cortex, neocortex and hippocampus. Repeated exposure to mitragynine increased delta, but decreased alpha powers in both cortical regions. It further decreased delta power in the hippocampus. These findings suggest that acute and chronic mitragynine can have profound effects on EEG activity, which may underlie effects on behavioral activity and cognition, particularly learning and memory function.
CRIS-Team Scopus Importer:2021-01-29
Keywords: EEG; Kratom; Mitragynine; Morphine